Draft Genome Sequence of Bacillus ginsengihumi Strain M2.11 with Phytase Activity - Toymentseva, Anna A. (Genome Announc, 2015)
This paper announces the genome sequence of Bacillus ginsengihumi strain M2.11, which has been characterized as a strain which produces the enzyme with the ability to degrade phytase. The genome of the strain M2.11 is 3.7 Mb and harbors 3,082 coding sequences.